Respiratory Syncytial Virus-Associated Hospitalizations in Young Children in the United States, 2015–2016. (4th October 2017) - Rha, Brian; Campbell, Angela P; McDaniel, Darius; Weinberg, Geoffrey A; Staat, Mary A; Selvarangan, Rangaraj; Halasa, Natasha B; Englund, Janet; Boom, Julie A; Azimi, Parvin H; Williams, John V; Szilagyi, Peter G; et al.
Abstract: Background: Respiratory syncytial virus (RSV) is a major cause of severe acute respiratory illness (ARI) among young children. With several vaccines and immunoprophylaxis agents for RSV currently in development, updated estimates of severe RSV disease in young children in the United States (US) are needed. Methods: Prospective active surveillance for hospitalized ARI was conducted from 11/1/2015 to 6/30/2016 among children <5 years of age at seven pediatric hospital sites participating in the New Vaccine Surveillance Network. Demographic and clinical information for enrolled subjects were gathered through parent interviews and medical chart reviews. Mid-turbinate nasal and throat flocked swabs (combined for testing when available) and/or tracheal aspirates (when pertinent) were collected for respiratory pathogen testing. Specimens were tested for RSV using molecular diagnostic assays at each site. Results: In preliminary data analyses, 2, 948 hospitalized children with a median age of 11 months were enrolled during the study period, of whom 1, 030 (35%) tested positive for RSV. Most RSV-detections occurred in children <2 years of age (87%; n = 893), with 340 (33%) RSV-positive children aged 0–2 months, 184 (18%) aged 3–5 months, 174 (17%) aged 6–11 months, and 195 (19%) aged 12–23 months. The majority of RSV-positive children (75%; n = 776) had no chart-documented comorbid conditions. Among 893 RSV-positive children <2 years of age, 161 (18%) reported a history of preterm birth, with 99 (11%) reporting birth at 34–36 weeks gestational age (WGA), 33 (4%) at 30–33 WGA, 20 (2%) at <30 WGA, and 9 (1%) with no further gestational age information available. Among all RSV-positive subjects, the median length of stay was 2 days; 706 (69%) received supplemental oxygen during hospitalization, 226 (22%) were admitted to an intensive care unit, and 28 (3%) required mechanical ventilation. Conclusion: During the 2015–16 season, RSV was associated with one-third of ARI hospitalizations in young children, the majority of which occurred in children aged <2 years. Most RSV-positive children were previously healthy, and nearly one fifth of those <2 years of age reported a history of preterm birth. RSV continues to be a major cause of morbidity among young children in the US. Disclosures: N. B. Halasa, sanofi pasteur: Research Contractor, Research support; Astra Zeneca: Research Contractor, Grant recipient; J. Englund, Gilead: Consultant and Investigator, Research support; Chimerix: Investigator, Research support; Alios: Investigator, Research support; Novavax: Investigator, Research support; MedImmune: Investigator, Research support; GlaxoSmithKline: Investigator, Research support; J. V. Williams, Quidel: Scientific Advisor, Consulting fee; GlaxoSmithKline: Scientific Advisor, Consulting fee; F. M. Munoz, Novavax: Investigator, Research support; Regeneron: Investigator, Research support; GSK: Investigator, Research support